Content validity of an educational workshop based on the Dietary Guidelines for the Brazilian Population - Constante JAIME, Patricia; Raulino TRAMONTT, Cláudia; de Mattos MAIA, Tarsis; Tiemann GABE, Kamila; Cardoso dos REIS, Lígia (Revista de Nutrição, 2023)
Objective To describe the development and validation of a workshop protocol for the implementation of the Dietary Guidelines for the Brazilian Population in primary healthcare units. Methods This descriptive study was developed in the state of São Paulo, Brazil, and it involved 20-25 professionals in the experimentation phase and 12 experts in the content validity phase. The workshop protocol was developed according to three theoretical references: Dietary Guidelines, Interprofessional Collaborative Practice and Critical Refl exive Methodology. The protocol consisted of four 4-hour modules, 16 activities in 16 hours. The activities matrix was composed of three axes: (a) organizational strategies, (b) dietary guideline comprehension and(c) dietary guideline implementation. For the validity analysis, the expert panel assessed clarity, relevance and theoretical representativeness. Content validity index was calculated, and adequate activities scored >0.80. The proportion of experts who recognized the presence of the theoretical framework in the activities was calculated. Results All 16 proposed activities obtained a score greater than the established cut-off point, both for clarity and relevance. For theoretical representativeness analysis, the dietary guidelines reached higher scores on the (b) and (c) axes of the protocol and was less recognized on the (a) axis, whose highest score was for the Critical Reflexive Methodology. Interprofessional Collaborative Practice presented a higher score on the (c) axis and a lower one on the (b) axis. Conclusion The protocol was considered appropriate for its purpose and with potential application in the different scenarios of primary health care in Brazil.